Functional capacity and quality of life of obese women from an interior in the state of Rio Grande do Norte - Santos, Ivanaldo Luna da Silva (2020)
Introduction: Obesity is a comorbidity that is associated with excessive and abnormal accumulation of body fat and is associated with adverse health effects such as the likelihood of psychological and social disorders, sleep disorder, depression, anxiety disorders, and distortion of body fat. body image, as well as being a risk factor for increased premature deaths and non-communicable chronic diseases (NCDs). Objective: To analyze the functional capacity and quality of life of obese women from an interior of the state of Rio Grande do Norte - Santa Cruz-RN. Materials and methods: Thirty female volunteers were recruited by signing the informed consent form. Physical capacity was assessed by the Incremental Shuttle Walking Test (ISTW) and the Six-Minute Walk Test (6MWT). Quality of life was assessed using the Short Form Health Survey (SF-36). Data were statistically analyzed using the Anova test for repeated samples with Post Hoc Bonferroni, according to the distribution of the variable, *p <0.05. For data analysis we used the program Graph Pad Prism version 5.0. Results: It was observed alteration in the predicted decrease of walking in the physical capacity test and in SF-36, decrease in the domain regarding the general state of health, pain and emotional aspects. Conclusion: Obese women had reduced physical capacity at submaximal exercise test, ISTW and 6MWT, as well as decreased general health, which interfere and compromise quality of life.